2017
DOI: 10.5505/tjtes.2017.59940
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Code Blue; can Apache II and PRISM scores be markers for prognostication?

Abstract: BACKGROUND: Code blue (CB) is an emergency call system developed to respond to cardiac and respiratory arrest in hospitals. However, in literature, no scoring system has been reported that can predict mortality in CB procedures. In this study, we aimed to investigate the effectiveness of estimated APACHE II and PRISM scores in the prediction of mortality in patients assessed using CB to retrospectively analyze CB calls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
(21 reference statements)
1
3
0
7
Order By: Relevance
“…Cicekci et al stated that 32.6% of the CB calls were in working hours [12]. Bakan et al reported that true CB calls were given often out of working hours (66.82%) [13]. In our study, we found this rate as 62.22 %.…”
Section: Dıscussıonsupporting
confidence: 53%
See 1 more Smart Citation
“…Cicekci et al stated that 32.6% of the CB calls were in working hours [12]. Bakan et al reported that true CB calls were given often out of working hours (66.82%) [13]. In our study, we found this rate as 62.22 %.…”
Section: Dıscussıonsupporting
confidence: 53%
“…Pembeci et al found that the survival rate was 49%[17]. Bakan et al reported this rate as 37.92%[13].…”
mentioning
confidence: 98%
“…The purpose of the Code Blue is to improve the success of CPR, and thereby improve the patient survival rate. The Code Blue includes the establishment of a professional team, maintaining the alertness of the team, technological call systems, preparation until the team arrives, the time to arrival of the Code Blue team, availability of equipment, and effective intervention and post-intervention management and records (11). Our training courses used a series of modularized, standardized, and practical teaching courses combined with theoretical learning, case teaching, skill training, and comprehensive assessment so that medical staff can accurately grasp the first aid theory and achieve improved resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Mavi kod (MK), hastanelerde kalp ve solunum durması vakalarına cevap vermek için geliştirilen bir acil çağrı sistemidir [2]. Mavi Kod genellikle, en sıklıkla KPA'nın bir sonucu olarak KPR gerektiren veya acil tıbbi yardım gerektiren bir hastayı tanımlamak için kullanılmaktadır [3].…”
Section: Introductionunclassified
“…[10]. Bir çalışmada, çağrılarının en sık iç hastalıkları servisi tarafından ve ardından ameliyathane tarafından yapıldığı bildirilmiştir [2]. Başka bir çalışmada ise, en sık çağrı yapılan yerlerin, flebotomi odaları ve ayakta tedavi kliniklerinin odaları olduğu ve bunları yatan hasta kliniklerinin ve invazif radyoloji kliniklerinin odalarının takip ettiği bildirilmektedir [3].…”
Section: Introductionunclassified